Chloride:Sodium Ratio May Accurately Predict Corrected Chloride Disorders and the Presence of Unmeasured Anions in Dogs and Cats - Goggs, Robert; Myers, Marc; De Rosa, Sage; Zager, Erik; Fletcher, Daniel J. (Frontiers in Veterinary Science, 2017)
Disorders of chloride and mixed acid–base disturbances are common in veterinary emergency medicine. Rapid identification of these alterations and the presence of unmeasured anions aid prompt patient assessment and management. This study aimed to determine in dogs and cats if site-specific reference values for [Cl−]:[Na+] ratio and [Na+] − [Cl−] difference accurately identify corrected chloride abnormalities and to evaluate the predictive ability of the [Cl−]:[Na+] ratio for the identification of unmeasured anions. A database containing 33,117 canine, and 7,604 feline blood gas and electrolyte profiles was generated. Institution reference intervals were used to calculate site-specific reference values for the [Cl−]:[Na+] ratio and the [Na+] − [Cl−] difference. Contingency tables were used to assess the ability of these values to correctly identify corrected chloride disorders. Unmeasured anions were estimated by calculating strong ion gap (SIG). Continuous variables were compared using the Mann–Whitney U test. Correlations between continuous variables were assessed using Spearman’s rho (rs). In dogs, site-specific reference values for the [Cl−]:[Na+] ratio correctly identified 94.6% of profiles as hyper-, normo-, or hypochloremic. For dogs with normal sodium concentrations, site-specific reference values for the [Na+] − [Cl−] difference correctly identified 97.0% of profiles. In dogs with metabolic acidosis (base deficit > 4.0), [Cl−]:[Na+] ratio and SIG were moderately but significantly negatively correlated (rs −0.592, P < 0.0001). SIG was significantly greater in dogs with metabolic acidosis and hypochloremia compared to those without hypochloremia (P < 0.0001). In cats, site-specific reference values for the [Cl−]:[Na+] ratio correctly identified 93.3% of profiles as hyper-, normo-, or hypochloremic, while site-specific reference values for [Na+] − [Cl−] difference correctly identified 95.1% of profiles. In cats with metabolic acidosis [Cl−]:[Na+] ratio and SIG were moderately significantly negatively correlated (rs −0.730, P < 0.0001). SIG was significantly greater in cats with metabolic acidosis and hypochloremia compared to those without hypochloremia (P < 0.0001). Site-specific values for [Cl−]:[Na+] ratio and [Na+] − [Cl−] difference accurately identify corrected chloride disorders in both dogs and cats and may aid identification of the presence of unmeasured anions.